2001
DOI: 10.1073/pnas.121085898
|View full text |Cite
|
Sign up to set email alerts
|

Antillatoxin is a marine cyanobacterial toxin that potently activates voltage-gated sodium channels

Abstract: M arine cyanobacteria represent a particularly rich source of structurally unique neurotoxic secondary metabolites (1-5). Lyngbya majuscula is a pantropical marine cyanobacterium that is the source of antillatoxin (ATX), a structurally unusual lipopeptide (1) (Fig. 1). Blooms of L. majuscula have been associated with adverse effects on human health. These blooms have been reported to cause respiratory irritation, eye inflammation, and severe contact dermatitis in exposed fishermen and swimmers (6). ATX has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 24 publications
3
74
0
Order By: Relevance
“…ATX has been demonstrated to allosterically stimulate [ 3 H]BTX binding in cerebellar granule cells [11]. This enhancement can be further augmented by PbTx-2 suggesting a positive allosteric interaction between neurotoxin site 5 and the ATX site [11]. In the present study we demonstrated that a subthreshold concentration of ATX significantly potentiated PbTx-2-induced sodium influx in rNa v 1.4 α-subunit expressing cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…ATX has been demonstrated to allosterically stimulate [ 3 H]BTX binding in cerebellar granule cells [11]. This enhancement can be further augmented by PbTx-2 suggesting a positive allosteric interaction between neurotoxin site 5 and the ATX site [11]. In the present study we demonstrated that a subthreshold concentration of ATX significantly potentiated PbTx-2-induced sodium influx in rNa v 1.4 α-subunit expressing cells.…”
Section: Discussionsupporting
confidence: 69%
“…ATX binds to a site on the sodium channel α-subunit that remains to be defined and stimulates sodium influx in cerebellar granule and neocortical neurons [11,12]. Veratridine is a steroid-derived alkaloid purified from the plant Liliaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological activity of such Lyngbya-derived compounds ranges from microtubule inhibitors, such as curacin A (Gerwick et al, 1994), to potent sodium channel blockers and activators, such as kalkitoxin (Wu et al, 2000) and antillatoxin (Li et al, 2001). On the other hand, exposure to Lyngbya toxins have also been associated with various human health effects (Izumi and Moore, 1987;Osborne et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some bloomforming cyanobacteria also produce toxins, which are actually more toxic to human and terrestrial mammals than to aquatic biota. Neurotoxins and hepatotoxins produced by some of the bloom-forming cyanobacteria, such as Nodularia (Laamanen et al 2001;Sivonen et al 1989) and Lyngbya majuscula (Li et al 2001), cause economic losses to the surrounding societies, ranging from disturbance in tourism due to the unpleasant smell, skin irritation and gastrointestinal problems of the swimmers, to death of fish and domestic animals drinking the water. Interestingly, and for an unknown reason, blooms of toxic cyanobacterial species may contain both toxic and non-toxic strains.…”
Section: Filamentous Planktonic Cyanobacteria: Bloom Formation and Tomentioning
confidence: 99%